Application of waste tyre rubber chips as coarse aggregate in concrete (Progressive Agriculture, 2020)
The practicality and the engineering properties of portland cement concrete (PCC) and three types of rubberized PCC mixes prepared by partially replacing the conventional coarse aggregate with rubber were examined. The rubberized PCC mixes contained 5%, 10% and 15% waste tyre rubber chips as replacement of conventional coarse aggregate. Different physical and mechanical properties of the control (0% rubber chips) and the rubberized concrete samples were determined. A 5% replacement of conventional aggregates resulted in a 5% reduction of compressive strength, a 10% replacement resulted in a 26% reduction and a 15% replacement resulted in a reduction of 47%. A 5% replacement of conventional aggregates resulted in a 6% reduction of tensile strength, a 10% replacement resulted in a 33% reduction and a 15% replacement resulted in a reduction of 53%. A 5% replacement of conventional aggregates resulted in a 13% reduction of flexural strength, a 10% replacement resulted in a 33% reduction and a 15% replacement resulted in a reduction of 42%. Although concrete made from tyres had lower strength than the normal concrete, rubberized concrete can find its use in landscaping, sports field ground, architectural finishing, lightweight concrete walls etc.Progressive Agriculture 30 (3): 328-334, 2019